Listen-search-read-discuss: an innovative lesson design to improve students’ scientific literacy in higher education - Junanto, Tulus; Budiyono, Budiyono; Akhyar, Muhammad; Suryani, Nunuk (International Journal of Evaluation and Research in Education (IJERE), 2024)
Scientific literacy enables prospective teachers to use science processes and products, allowing them to engage in scientific discussions about social issues. The listen-search-read-discuss (LISERED) learning model was developed by researchers to enhance scientific literacy. This study aimed to assess the implementation of the LISERED model in improving students’ scientific literacy skills. The research followed a quasi-experimental design with pretest and post-test control groups. The study collected data on scientific literacy in chemistry education programs, involving 62 students as samples. The efficacy test utilized a written multiple-choice test, specifically the test of scientific literacy skills (TOSLS). The results indicated a high effect size (ES) for the LISERED model in enhancing scientific literacy mastery (ES Cohen=2.859; ES Hedges=2.824; and ES Glass=3.285). This model facilitates a more interactive and engaging learning environment, enabling students to develop a deeper understanding of science. Implementing the LISERED model empowers teachers to significantly enhance students’ scientific literacy comprehension.